PENGUATAN LITERASI ANAK MELALUI PEMBENTUKAN TAMAN BACA MASYARAKAT DI DESA TAMBAKREJO - Rifqi Firdaus; Bella Arini Haq (LPPM STAI Muhammadiyah Probolinggo, 2025)
Literacy is the basic ability to read, write, understand, and process information, which serves as an important foundation for lifelong learning. For children, literacy is crucial because it not only supports academic success but also develops critical and creative thinking patterns and the life skills needed for the future. Strengthening children's literacy through the establishment of Community Reading Gardens is a strategic effort to provide easily accessible reading access while creating an inclusive learning environment. The presence of reading gardens plays a crucial role in fostering reading interest, improving literacy skills, and supporting the creation of a culture of literacy within the community. Efforts to improve children's literacy in Tambakrejo Village are realized through the establishment of Community Reading Gardens, which provide easily accessible learning and reading spaces. The role of the Children's Forum as the driving force of activities also strengthens this program through mentoring and managing creative and participatory literacy activities. The synergy between the two parties is an important foundation in fostering a reading culture and expanding learning opportunities for children in the village.